Implementasi E-Learning Berbasis Moodle di Masa Pandemi Covid 19 - Kristina Sara; Ferdinandus Lidang Witi; Anastasia Mude (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the results of the implementation of moodle-based e-learning. This type of research is a descriptive analysis with a frequency distribution, namely concluding based on the data obtained during the study. The research sample was 71 people. The results of the study found that there were 19.3% of students who answered strongly agree; 61.5% of students who answered agreed; 16.4% answered disagree 2.7% answered strongly disagreed with using moodle-based e-learning during the Covid-19 pandemic. For some students who answered disagree and strongly disagreed, it was because the student concerned did not yet have a laptop and their place of residence was far from urban areas. In conclusion, the use of moodle-based e-learning is very appropriate, in order to overcome conventional learning activities that cannot be done due to the COVID-19 pandemic and the availability of facilities and infrastructure is very much needed so that learning outcomes can be realized. Keywords: e-Learning, Moodle